“Liikumisega” vene laulude kultuurilisi tähendusi Udmurdimaa Debjossõ rajooni Varni külas - Svetlana Tolkachova (Mäetagused)
The aim of this article is to identify the specific features of the functioning of Russian round dance and dance songs in the traditional culture of the Northern Udmurts. Four songs in Russian, recorded from Udmurt performers by Tatiana Vladykina in the village of Varni, Debessky district of Udmurtia, in 1981 were chosen for the study: “My zaganem sem’ zagadok”, “Pri dolinke voda”, “…Tropitsa, kanapel’ kalotitsa”, “Chornyi voron vodu pil”. The correlation of these songs with Russian songs of the round dance tradition in the Kama-Vyatka interfluve allows classifying them as “songs with movement”. The analysis of the musical and poetic stylistics of the songs and the cultural context of their performance reveals that in Udmurt folklore, Russian round dance and dance songs exist parallel to the well-established core of sacral clan chants specific to the Udmurts. At the same time, a trend of assimilating Russian “songs with movement” has emerged in the traditional musical culture of the Northern Udmurts, to the extent that some of them have acquired a sacral meaning. These trends in the existence of round dance and dance songs in Russian in the Northern Udmurt dialect traditions are linked to a collective, unifying element, the festive atmosphere, and the perception of Russian round dance songs as a “borderline” genre. Yet another trend applies to the practice of performing round dance songs at a slow tempo. For the performance of these songs, singers demonstrate a more personal approach to the reproduced sonic fabric, expressing their individuality and uniqueness at the sound level. The singing of some slow Russian round dance songs by the Northern Udmurts turns out to be consonant with the performances of krezes in terms of musical-rhythmic parameters. The third tendency, the incorporation of slow round dance songs with Russian lyrics into Udmurt rituals, is also connected with the inherent possibility of endowing the sound canvases of such songs with “special” timbral, acoustic, and metric-rhythmic qualities characteristic of indigenous Udmurt ritual songs and “harmonious” with the musical expression of Udmurt rituals.